2011
DOI: 10.1074/jbc.m111.230854
|View full text |Cite|
|
Sign up to set email alerts
|

Homeodomain-interacting Protein Kinase-2 Stabilizes p27kip1 by Its Phosphorylation at Serine 10 and Contributes to Cell Motility

Abstract: HIPK2 is a serine/threonine kinase that acts as a coregulator of an increasing number of factors involved in cell survival and proliferation during development and in response to different types of stress. Here we report on a novel target of HIPK2, the cyclin-dependent kinase inhibitor p27 kip1 . HIPK2 phosphorylates p27 kip1 in vitro and in vivo at serine 10, an event that accounts for 80% of the total p27 kip1 phosphorylation and plays a crucial role in the stability of the protein. stability. An initial eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Overexpression of DYRK1A increased Ser10 phosphorylation similar to HIPK2, which is known to phosphorylate p27 Kip1 at Ser10. 14 Inhibition of endogenous DYRK1A with a harmine-related DYRK1A inhibitor (AnnH31, unpublished results) reduced basal Ser10 phosphorylation compared with the untreated control ( Fig. 8C ).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Overexpression of DYRK1A increased Ser10 phosphorylation similar to HIPK2, which is known to phosphorylate p27 Kip1 at Ser10. 14 Inhibition of endogenous DYRK1A with a harmine-related DYRK1A inhibitor (AnnH31, unpublished results) reduced basal Ser10 phosphorylation compared with the untreated control ( Fig. 8C ).…”
Section: Resultsmentioning
confidence: 84%
“…In order to assess whether DYRK1A contributes to p27 Kip1 Ser10 phosphorylation in differentiating brain neurons, we cultured E12 embryos for 6 h in the presence of EGCG, harmine, and leucettine L41, 3 different and chemically unrelated DYRK1A inhibitors. 47 This time period is substantially shorter than the duration of a cell cycle, which at this stage has been estimated to last for 20–24 h. 4 , 48 Harmine, EGCG, and leucettine L41 have been profiled against large panels of protein kinases 47 and do not inhibit the other kinases that are known to phosphorylate p27 Kip1 at Ser10 (KIS, AKT, CDK5, HIPK2) 11 - 14 , 49 except for DYRK1B, which is a regulator of p27 Kip1 in cancer cells. 15 , 50 All 3 DYRK1A inhibitors substantially decreased pSer10 p27 Kip1 immunostaining in the mouse telencephalon ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we performed in vitro kinase assays to assess the Ser/Thr kinase activities of the Tyr→Phe mutants towards exogenous substrates. First, we used recombinant p27 Kip1 as a substrate, because this CDK inhibitor had been shown to be a substrate of HIPK2 [ 40 ]. These assays showed that all HIPKs are capable of phosphorylating Ser10 in p27 Kip1 in vitro (Figure 4 A).…”
Section: Resultsmentioning
confidence: 99%
“…46 Recently, HIPK2 has also been shown to phosphorylate Ser10 and stabilize p27 in asynchronously growing cell lines. 47 Further work will be necessary to uncover the contribution of the individual kinases in different cell types and different phases of the cell cycle.…”
Section: Dyrk2 Initiates Protein Degradation Via the Upsmentioning
confidence: 99%